Israel : Staff Report for the 2006 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This 2006 Article IV Consultation highlights that strong macroeconomic conditions and sound domestic policies have significantly improved Israel's growth performance and prospects, notwithstanding political uncertainties and the hostilities in the north during the summer of 2006. Inflation pressures are subdued, and monetary policy has been easing as of late. Financial soundness indicators have been recovering although some weaknesses on bank balance sheets that relate mainly to previous boom-bust cycles remain. For 2007, real GDP growth is forecast about 4 1\2 percent.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet